Comparison of corrosion protection between double strands of polyaniline and poly-o-anisidine with poly(Acrylic Acid-Co-Acryl Amide) on steel - Mahmoudian, M.R.; Alias, Y.; Basirun, Wan Jefrey (Springer Verlag, 2012)
Double strands of polyaniline (PAn) and poly(o-anisidine) (POAn) with poly(acrylic acid-co-acryl amide) (PAA-co-AA) were successfully prepared on steel as undercoating, by immersion of the pretreated surfaces into a PAn: (PAA-co-AA) and POAn: (PAA-co-AA) saturated DMF solution separately. The undercoatings formed on the steel were characterized by Fourier transform infrared spectroscopy (FTIR) techniques. A commercial paint (Nippon Paint, nonadded Chrome) was used as topcoating. Electrode/electroactive polymer/paint/electrolyte system was studied by electrochemical impedance spectroscopy (EIS). The EIS studies show that during the first 18 days immersion time in 3.5% solution of NaCl, paint/PAn coating has better corrosion resistance than paint/POAn coating while in the final week of immersion time, the pore resistance (R-po) and coating capacitance (C-c) of paint/POAn are higher and lower than the paint/PAn, respectively.